Double-Blind Clinical Trial of Arginine Supplementation in the Treatment of Adult Patients with Sickle Cell Anaemia - Renata M. N. Eleutério; Francisco O. Nascimento; Tamara G. Araújo; Marilena F. Castro; Tarcísio P. Almeida Filho; Pedro A. Maia Filho; José Eleutério; Darcielle B. D. Elias; Romélia P. G. Lemes (Advances in Hematology)
Background. Sickle cell anaemia (SCA) is the most prevalent monogenic disease in Brazil. In SCA, haemoglobin S (HbS) is formed, which modifies red blood cell morphology. Intravascular haemolysis occurs, in which free Hb and free radicals degrade nitric oxide (NO) and release arginase, which reduces arginine levels. Because arginine is a substrate for NO formation, this decrease leads to reduced NO (vasodilator) synthesis. SCA treatment uses hydroxyurea (HU) to maintain high foetal haemoglobin (HbF) levels and reduces HbS to avoid haemolytic episodes. Objective. To analyse the efficacy of L-arginine as an adjuvant in the treatment of SCA patients. Setting. The State Blood Centre of Ceará, Brazil. Methods. This was a randomized double-blind clinical study of adults with SCA with continuous use of HU at the State Blood Centre of Ceará. The clinical study enrolled 25 patients receiving HU + L-arginine (500 mg) and 25 patients receiving HU + placebo. The treatment was carried out over four months. Laboratory tests were performed to determine the levels of the following: (1) complete blood count; (2) nitrite + nitrate; (3) HbF; and (4) reticulocytes. The clinical experiments were performed by a haematologist. The main outcome measures were nitrite and pain. Results. Statistical analysis showed that the levels of NO were increased in the study group, and there was also a reduction in pain frequency using a pain frequency scale by day, week, and month. The levels of nitrite plus nitrate in the group receiving placebo plus HU did not change among the times evaluated (38.27 ± 17.27 mg/L, 39.49 ± 12.84 mg/L, 34.45 ± 11.25 mg/L, p >0.05), but in the patients who received supplementation with L-arginine plus HU, a significant increase in nitrite plus nitrate levels was observed between M0 and M4 (36.55 ± 20.23 mg/L versus 48.64 ± 20.63 mg/L, p =0.001) and M2 and M4 (35.71 ± 15.11 mg/L versus 48.64 ± 20.63 mg/L, p <0.001). It is important to note that the increase in nitrite plus nitrate levels occurred only in the fourth month of follow-up of patients in the treatment group, showing that at least 4 months of supplementation with L-arginine is necessary to show an increase in these metabolites in the serum. Conclusion. The use of L-arginine as a coadjuvant in the treatment of sickle cell anaemia may function as a potential tool for pain relief, consequently improving the life of patients.